An experimental setup investigation to study characteristics of fault on transmission system - Yindeesap, P.; Ngaopitakkul, A.; Pothisarn, C.; Jettanasen, C. (My University, 2015)
This paper proposes the experimental setup for studying the characteristics of fault caused by balance and unbalance on a transmission system. The parameters of transmission system (inductance and capacitance) are calculated based on forms of transmission tower, size of conductor, types of conductor and arrangement of transmission line and, they normalized to obtain the values in the π- equivalent circuit model at voltage level of 400 V. In addition, the ATP/EMTP is used to compare the simulated results with the experimental setup in order to show the advantage of the experimental setup. The obtained results show that the similarity between the two waveforms. The experimental setup will be useful in the development of short-circuit protection system in laboratory.
Keywords: ATP/EMTP; Experimental setup; Fault; Transmission line